Brooks Schramm and Kirsi I. Stjerna. Martin Luther, the Bible, and the Jewish People: A Reader. Eric W. Gritsch. Martin Luther’s Anti-Semitism: Against His Better Judgment - Sherman, Franklin (Studies in Christian-Jewish Relations, 2013)
No abstract is available.